Effect Of Inulin On Oral Bioavailability Of Minerals And Drugs - Ong, Hwee Ching (2010)

(untitled)
The present study was conducted to evaluate the potential and effect of different doses of inulin in enhancing the oral absorption of zinc and magnesium. The effect of different doses of inulin in the oral bioavailability of the 2 model drugs, acyclovir and atenolol, was also assessed. Prior to the study, two simple, rapid and sensitive flame atomic absorption spectrophotometer methods were successfully developed for the determination of zinc and magnesium in rat plasma, respectively. The accuracy values were between 91 – 107% for zinc and 92 – 105% for magnesium, while the coefficient of variation values were all less than 12.5% for both zinc and magnesium.